Overgrowth and killing of corals by the brown alga Lobophora hederacea (Dictyotales, Phaeophyceae) on healthy reefs in New Caledonia: A new case of the epizoism syndrome. Issue 2 (28th January 2015) - Vieira, Christophe; Payri, Claude; De Clerck, Olivier
Summary: Coral reef degradation is often associated with regime shifts from coral‐ to macroalgal‐dominated reefs. These shifts demonstrate that under certain conditions (e.g. coral mortality, decrease in herbivory, increased nutrients supply) some macroalgae may overgrow corals. The outcome of the competition is dependent on algal aggressiveness and the coral susceptibility. In undisturbed reefs, herbivore grazing is regulating macroalgal cover, thus preventing the latter from overgrowing corals. However, some macroalgae have evolved strategies not only to outcompete corals but also to escape herbivory to some extent, allowing overgrowth of some coral species in undisturbed reefs. Epizoism represents one of those successful strategies, and has been previously documented with red algae, cyanobacteria and Lobophora variegata (Dictyotales, Phaeophyceae). Here we report a new case of epizoism leading to coral mortality, involving a recently described species of Lobophora, L. hederacea, overgrowing the coral Seriatopora caliendrum (Pocilloporidae) in undisturbed reefs in New Caledonia.